Pembentukan Flavor Bubuk Cokelat, Kajian Peranan Waktu Fermentasi Biji Kakao - G.P. Ganda Putra; Sutardi Sutardi; Bambang Kartika (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1992)
This research Investigated the role of cocoa bean fermentation to the formation of specific flavor of cocoa powder. Periode of fermentation varies from 0 hour (without fermentation) up to 192 hours. The degree of fermentation index increased from 0.38 at the,beginning of fermentation to 1.26 at 168 hours fermentation. The flavor formation of cocoa powder was characterized by decreasing of pH, total polyphenol and theobromine content during fermentation of cocoa beans. The chromatogram profile of components constituiting the odor of cocoa powder obtained from different fermentation penode were similar. However, each cocoa powder having different components for formation of odor gave different response on peaks; particularly on peaks number 3 and 5 which achieved maximum area during 72 and 144 hours fermentation, respectlvery. While, the other components (peak number 1, 2 and 4) were slightly change.